Soundbite nas cibernotícias das rádios : um estudo sobre a duração e função do áudio nos conteúdos jornalísticos na internet - Reis, Ana Isabel Crispim Mendes (2012)
The average listener's attention has been declining in recent decades especially, calculating that these days a young person has much less ability to concentrate hearing their parents: less than two minutes instead of eight recorded in the 60 decade (Meditsch, 1999). This factor combined with the voracious consumption, immediate and ever faster information influences the sound on journalistic content? The audio on webradios tends to be a short soundbite? The aim of this study is to determine whether the referred soundbite culture actually exists in the audios of news sites of radio and if the audio has a complementary information regarding the text. We analyzed the Portuguese websites of TSF, Rádio Renascença, RDP and RCP at random periods for three years and we may say that they did not join the soundbite culture in journalistic content.